2005
DOI: 10.1093/protein/gzi009
|View full text |Cite
|
Sign up to set email alerts
|

Protein sequence entropy is closely related to packing density and hydrophobicity

Abstract: We investigated the correlation between the Shannon information entropy, 'sequence entropy', with respect to the local flexibility of native globular proteins as described by inverse packing density. These are determined at each residue position for a total set of 130 query proteins, where sequence entropies are calculated from each set of aligned residues. For the accompanying aggregate set of 130 alignments, a strong linear correlation is observed between the calculated sequence entropy and the corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 54 publications
3
81
0
Order By: Relevance
“…It was previously observed that this measurement is directly related to the structure of the protein [30]. Regions with higher sequence entropy (i.e.…”
Section: Epitopes Are Found Adjacent To Variable Sequencesmentioning
confidence: 92%
“…It was previously observed that this measurement is directly related to the structure of the protein [30]. Regions with higher sequence entropy (i.e.…”
Section: Epitopes Are Found Adjacent To Variable Sequencesmentioning
confidence: 92%
“…It has been confirmed that evolutionarily conserved residues in a protein are responsible for its function, stability and/or structural formation [30][31][32][33][34][35]. In this study, we attempt to identify conserved hydrophobic residues.…”
Section: Evolutionary Analysismentioning
confidence: 98%
“…protein-protein interaction ͉ hot spots in the interface ͉ residue conservation ͉ crystal packing ͉ quaternary structure prediction E volutionary conservation of amino acid residues may include active-site residues pertaining to the function of the molecule or tightly packed sites contributing to the stable core or indicative of the folding nucleus (1)(2)(3)(4). For cellular function proteins need to interact with other molecules, and techniques such as the twohybrid system and affinity purifications are being used to discover the physical association between proteins, leading to a fascinating view of cell-interaction maps (5,6).…”
mentioning
confidence: 99%